Identification of superior cowpea varieties in competition with weeds - Medeiros, Isis Fernanda; Silva, Paulo Sérgio; Sousa, Roberto; Siqueira, Patrícia Liany; Oliveira, Vianney (Revista Ciência Agronômica, 2021)
Cowpea varieties that are more competitive against weeds are, by themselves, not enough to control the weeds. However, the adoption of more-competitive varieties, together with other cropping practices, including planting density and weeding, can provide greater weed control in addition to affording the farmer more time to carry out this control. This study had the following objectives: a) to identify, in a preliminary evaluation (E-1), varieties that are the most competitive against weeds, based on dry grain yield; b) among the most-competitive varieties, identify the most productive in terms of green and dry grain yield (E-2). The seeds used for E-1 were obtained from producers chosen at random from each of 48 districts in the State of Rio Grande do Norte. A randomized block design with five replications was used. In E-2, the twelve varieties presenting the highest grain yield in E-1 were evaluated in a randomized block design with five replications. In both evaluations, only one weeding was carried out, 30 days after sowing. In E-1, the Umarizal, Itaú, Upanema, Lagoa de Pedras, José da Penha and São Tomé varieties were superior. The second experiment demonstrated that Umarizal is the most productive variety in terms of pod yield and green grain. There is no difference between the varieties for dry grain yield. The Umarizal variety has potential for use in the production of green pods and grains, and of dry grains. The preliminary evaluation is effective in identifying superior varieties.